2021
DOI: 10.7554/elife.67713
|View full text |Cite
|
Sign up to set email alerts
|

Finger somatotopy is preserved after tetraplegia but deteriorates over time

Abstract: Previous studies showed reorganised and/or altered activity in the primary sensorimotor cortex after a spinal cord injury (SCI), suggested to reflect abnormal processing. However, little is known about whether somatotopically-specific representations can be activated despite reduced or absent afferent hand inputs. In this observational study we used functional MRI and an (attempted) finger movement task in tetraplegic patients to characterise the somatotopic hand layout in primary somatosensory cortex. We furt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 93 publications
(192 reference statements)
3
36
2
Order By: Relevance
“…More specifically, there was stronger index compared to little finger activity on the lateral part of S1, while there was stronger little compared to index finger activity medial of S1. These S1 activity maps are in line with previous findings on finger somatotopy which is highly specific within S1 (Besle et al, 2013;Kikkert et al, 2021;Kolasinski et al, 2016;Martuzzi et al, 2014;Sanchez Panchuelo et al, 2018;Sanders et al, 2019). Finally, we assessed whether finger-specific activity was sustained within these finger-specific maps during the delay period.…”
Section: Vibrotactile Working Memory Recruits a Distributed Brain Networksupporting
confidence: 83%
“…More specifically, there was stronger index compared to little finger activity on the lateral part of S1, while there was stronger little compared to index finger activity medial of S1. These S1 activity maps are in line with previous findings on finger somatotopy which is highly specific within S1 (Besle et al, 2013;Kikkert et al, 2021;Kolasinski et al, 2016;Martuzzi et al, 2014;Sanchez Panchuelo et al, 2018;Sanders et al, 2019). Finally, we assessed whether finger-specific activity was sustained within these finger-specific maps during the delay period.…”
Section: Vibrotactile Working Memory Recruits a Distributed Brain Networksupporting
confidence: 83%
“…Consistent with this notion, previous functional magnetic resonance imaging (fMRI studies have not detected the presence of planning-related information in this area Gallivan et al, 2011a ; Gallivan et al, 2011b , Gallivan et al, 2016 ; Gallivan et al, 2013 ; although see Gale et al, 2021 ). However, challenging this notion, in the past years research has shown that S1 can be somatotopically activated even in the absence of tactile inputs, for instance during touch observation ( Kuehn et al, 2014 ), attempted movements without afferent tactile inputs ( Kikkert et al, 2021 ), and through attentional shifts ( Puckett et al, 2017 ). Moreover, a recent human electrocorticography (ECoG) study suggested a possible role for S1 in cognitive-motor imagery ( Jafari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…was highly similar to the inter-finger representational distance patterns that we and others have described previously in fMRI experiments using individual finger movements (Ejaz et al, 2015;Kikkert et al, 2021Kikkert et al, , 2016Sanders et al, 2019;Wesselink et al, 2019) or individual finger tactile stimulation (Sanders et al, 2019). The inter-finger representational distances were averaged across finger pairs within each participant to obtain an estimate for average interfinger representational separability (see Figure 5C), or 'representation strength'.…”
Section: Finger Representationsmentioning
confidence: 53%
“…3 participants were stimulated on the right side of the face and their right thumb. We included thumb stimulation in these runs as the thumb representation borders the face area in S1 (Kikkert et al, 2021(Kikkert et al, , 2016Kolasinski et al, 2016;Penfield and Rasmussen, 1950;Roux et al, 2018). To uncover face somatotopy we used a blocked design consisting of 5 conditions: Stimulation conditions for each of the three face locations and for the thumb, as well as a rest (no stimulation) condition.…”
Section: Face Stimulation Runsmentioning
confidence: 99%